A method for obtaining aqueous and dry ethanol extracts of grass (a mixture of flowers with leaves) and a stalk of St. John's wort (Hypericum perforatum L.) with inhibitory activity on the replication of the SARS‐CoV‐2 coronavirus in vitro - Е. I. Каzachinskaia; Yu. V. Коnonova; A. V. Ivanova; L. N. Zibareva; А. А. Chepurnov; V. V. Romanyuk; A. A. Biibolatov; М. А. Gulyaeva; А. М. Shestopalov (Юг России: экология, развитие, 2023)
Aim. In vitro evaluation of the inhibitory activity of aqueous extracts and dry ethanol extracts of St John's wort (Hypericum perforatum L.) on the replication of SARS-CoV-2 according to three experimental schemes – direct inactivation (neutralisation) of the virus as well as "prevention" and "treatment" of cells.Materials and Methods. The laboratory strain SARS-CoV-2/human/RUS/Nsk-FRCFTM-1/2020 was passed on Vero cell culture. Water extracts and dry ethanol extracts of parts of H. perforatum L. collected during the flowering period in the Novosibirsk region were prepared. Dry extracts were dissolved in DMSO. Comparison samples are dry ethanol extracts of chaga, cloves and black tea.Results. It is shown that the aqueous extract of grass (a mixture of flowers with leaves) of H. perforatum L. with direct inactivation of the virus it is active in dilution of 1/4096. For the dry ethanol extract of the herb H. perforatum L., 50 % effective concentrations (EC50) were found equal to 2.44±0.87; 8.79±1.91 and 14.65±1.91 μg/ml respectively with direct inactivation as well as according to the "preventive" scheme and with the "treatment" of cells. Taking into account cytotoxicity, as well as in comparison with control samples, the values of selective indices (SI50) of the studied herbal preparations during direct inactivation were higher than with other experimental schemes and were distributed as follows (in descending order): 204.92; 153.68; 115.27; 32.01 and 21.33 for dry ethanol extracts of black tea from India, cloves, herbs, a mixture of flowers with leaves, of H. perforatum, chaga and the stems of H. perforatum respectively. The HPLC method has shown that the ethanol extract of the herb H. perforatum L. contains a greater amount of flavonoids than the extract of stems. Nevertheless, antiviral activity was also detected for the extract of stems of this plant with EC50 equal to 14.65±1.91; 78.13±20.05 and 117.19±15.31 μg/ml (according to three experimental schemes), respectively.Conclusion. For the preparation of antiviral drugs the whole plant of H. perforatum L., including stems, can be used as raw materials.